The development and distribution of heavy mineral concentrations in alluvial systems - Lynn, Michael David (Rhodes University, Faculty of Science, Department of Geology, 1992)
The objective of this review is to summarise the characteristics, significance and evolution of heavy minerals and their accumulations, and to identify the key controls on the development and distribution of heavy mineral concentrations in alluvial systems. These controls can be broadly classified as tectonic setting, geomorphic setting and grain-scale concentrating processes, each of which is discussed. Based on this review, exploration models are developed which are designed to indicate favourable localities for the accumulation of heavy minerals, and trends likely to be exhibited within these accumulations. The models are structured from the broadest scale of target selection, down to the local scale of sample site selection. The major conclusion of this work is that an understanding of process geomorphology is required to develop genetic models of placer development, including a detailed evaluation of climatic fluctuations throughout the Caenozoic. Palaeoplacers such as the Witwatersrand goldfield, are inferred to have formed under similar circumstances of tectonic setting as genetically comparable Caenozoic placers such as those of Otago, New Zealand. The means of preservation of such major basins is however poorly understood.
Keywords: Heavy minerals -- Research; Alluvial plains -- Research; Geomorphology -- South Africa